Kontribusi Minat Belajar Dan Adversity Quotient Terhadap Hasil Belajar Matematika Siswa Kelas Xi Ipa Man 1 Surakarta Tahun Pelajaran 2014/2015 - Arby, Nur Taqiyyannisa'; , Drs. Ariyanto, M. Pd (2016)
Intention of this research is to analyse and test: (1) enthusiasm contribution learn to result learn mathematics, (2) adversity quotient contribution result of learning mathematics, (3) enthusiasm contribution and adversity quotient learn student mathematics. This research type quantitative with design research asosiatif. Research population 165 XI IPA MAN I class student Surakarta. Taken sampel XI class student HE IS 4 counted 33 students. Technique in take sampel use sample random sampling.technique data collecting with enquette method and documentation. Technique analyse data use double linear regression with signifikansi level 5%. Equation regresi with correlation coefficient 0,238 and have which is determinasi coefficient low with 5,7%. Pursuant to result of research obtained: (1)no enthusiasm contribution learn to result learn mathematics, (2)no adversity quotient contribution result of learning mathematics, (3)no enthusiasm contribution and adversity quotient learn student mathematics.